How Mediation Works: Resolving Conflict through Talk Angela Cora Garcia (2019) - Boluwaduro, Eniola (Sociolinguistic Studies, 2021)
How Mediation Works: Resolving Conflict through Talk Angela Cora Garcia (2019) Cambridge: Cambridge University Press ISBN: 978-1-107-02427-4 (hardback) 019015694 (eBook). Pp. 272